Чернігівщина років Голодомору (1932–1933) на сторінках часопису «Вісті ВУЦВК»: від пошуку «класово-ворожого» елементу до розвитку промисловості, торгівлі, освіти - Горох, М.В. (Сіверщина в історії України, 2025)
Одним із основних інструментів пропаганди, які активно використовував комуністичний тоталітарний режим, була преса. Центральна преса досліджуваного періоду, яка представлена газетою «Вісті ВУЦВК», є специфічним історичним джерелом, опрацювання якого вимагає детальної верифікації. Часопис містить багатий джерельний потенціал щодо вивчення процесів примусового вилучення продовольчих культур у селян, так званих хлібозаготівель, боротьби з «класово-ворожим» елементом, змінами в промисловості, торгівлі, соціальній, освітній та культурних сферах, що відбувалися в складних, часто несумісних з життям, умовах голоду. Газета «Вісті ВУЦВК» рясніла матеріалами локальної (місцевої) історії, зокрема Чернігівщини. One of the propaganda tools used by communist totalitarian regime was the press. It helped to implant the mass campaigns and political decisions which were necessary for the regime. «Visti VUTSVK» is a specific historical source which represents the central press of the researched period. It still needs the detailed verification. The magazine has depicted various topics concerning politics, economy, education, cooperation, social and female issues, global problems. Its contributions are the unique source for studying the different aspects of Holodomor (1932–1933). In the middle of the research are the publications dedicated to the struggle against the «class-hostile» element, changes in industry, transport, trade and construction, and educational needs. The «Visti VUTSVK» contributors devoted many articles and reports to these topics. Exposing criminals, accusing saboteurs and enemies of the Soviet regime, the newspaper occasionally correlated the identified shortcomings or violations with the real state of affairs in the countryside and in cities affected by the famine. Nevertheless, the information provided on its pages is a valuable source for local history, as it allows us to understand how historical events affected people’s lives in a particular period of time, in a particular place.